TRADISI AKADEMIK DALAM KHALAQAH TAFSIR (Orientasi Semantik al-Quran Klasik dalam Diskursus Hermeneutik) - Syamsul Wathani (MAGHZA, 2016)
This article discusses the Qur’anic semantic within hermeneutic discourse. The classical interpretation of the Qur’an (I-IV H) is set to be the subject matter to be discussed within the framework of hermeneutic. By doing so, the article is expected to contribute to giving a new formulation of the classical interpretation discourse on the Qur’an. Besides, the article is also expected to discover the new theory about Qur’anic hermeneutic which operated in the sphere of text. The classical Qur’anic semantic has shown the contestation which not only did it appear in the sphere of meaning (dilalah), but more deeply in played a dialectics of language between oral notion (al-Qur’an/kalam) and the recipient (khitab al-Qur’an).